Carbon footprint of a third-generation cryptocurrency – Cardano and comparison with other cryptocurrencies and traditional banking system - Koju, Narendra (2025)
The aim of this study was to assess the carbon footprint of the cryptocurrency- Cardano. This study addressed three questions: 1) What is the carbon footprint of Cardano? 2) How does the energy consumption of Cardano affect its overall environmental sustainability? and 3) How does the carbon footprint of Cardano compare with that of earlier-generation cryptocurrencies and the traditional banking system?